THE INFLUENCE OF PROFIT SHARING RATIO ON NUMBER OF MUSYARAKAH FINANCING CUSTOMERS (Case Study PT. BPRS Bhakti Sumekar) - mujibno mujibno; Ikawati Ikawati (Institut Dirosat Islamiyah Al-Amien Prenduan, 2020)
The purpose of this study was to determine whether or not there is an influence given by the profit sharing ratio on the number of musharaka financing customers. The results of this study indicate the profit-sharing ratio variable with a significance value of 0.000 <0.05, which means that the independent variable has a positive effect on the dependent variable and Tcount (5.343) > from Ttable (2.03452), so it can be concluded partially (t-test) there is a significant positive effect. from the profit-sharing ratio to the number of musyarakah financing customers and based on the results of the coefficient of determination (R2), a value of 0.456 is obtained, which means the effect of the profit-sharing ratio on the number of musyarakah financing customers is 45.6%, while 54.4% is influenced by other factors